STUNTING PADA KONDISI RAWAN PANGAN, SANITASI, DAN KELAYAKAN SUMBER AIR MINUM PADA KELUARGA DI PROVINSI BANTEN (ANALISIS DATA SSGI-2021) - Yenie Wulandari; Ismiyati Ismiyati (Jurnal Medikes (Media Informasi Kesehatan), 2023)
Stunting is still a special concern, despite a decrease in cases from year to year. This decline has not yet reached the national target of 14% by 2024. The purpose of this study was to determine the incidence of stunting based on food insecurity conditions, sanitation feasibility, and feasibility of family minimum water sources. The method used in this research is quantitative. The data used comes from the results of the Indonesian Nutrition Status Survey (SSGI) in 2021. The data used is specific to the Banten Province area. The number of samples used was 3671 families with children under five years old. Data analysis using chi-square. The incidence of stunting is associated with food insecurity, an environment with vulnerable sanitation, and unhealthy drinking water sources. Food-insecure families have a 1.5 times risk of having stunted toddlers. Meanwhile, families that do not have proper sanitation will have a risk of stunting of 2.174 times. A healthy environment with proper sanitation will certainly reduce toddlers from infections caused by the environment.